FLOWERING PERIOD OF THREE SPECIES OF PRUNUS COLLECTION IN CIBODAS BOTANIC GARDEN - Suluh Normasiwi (Pusbindiklat - LIPI, 2015)
This study aims to explore the flowering period of three species of Prunus collection in Cibodas Botanic Garden during the four-year period (time series 2009–2012). This flowering data is able to give an information about Prunus flowering ability, which later can improve the amount of Prunus collection through cross breeding and seed collection. Those three Prunus species are Prunus arborea, Prunus costata, and Prunus cerasoides. The result indicated that P.arborea has the rarest flowering cycle compares to other Prunus species On the other hand, P.costata has the most active flowering cycle, which is around 3–4 times/year and it is often followed by development of fruit set and seeds, and P.cerasoides flowering cycle is twice a year, but it is rarely followed by seeds development. The current habitat is more suitable for P. arborea’s flowering and fruiting initiation than for the other two Prunus’. Light intensity induced flowering initiation, while fruit and seed development were influenced by rainfall, air temperature, and other factors such as pollinator.